2013
DOI: 10.1089/hum.2013.137
|View full text |Cite
|
Sign up to set email alerts
|

Postentry Processing of Recombinant Adeno-Associated Virus Type 1 and Transduction of the Ferret Lung Are Altered by a Factor in Airway Secretions

Abstract: We recently created a cystic fibrosis ferret model that acquires neonatal lung infection. To develop lung gene therapies for this model, we evaluated recombinant adeno-associated virus (rAAV)-mediated gene transfer to the neonatal ferret lung. Unlike in vitro ferret airway epithelial (FAE) cells, in vivo infection of the ferret lung with rAAV1 required proteasome inhibitors to achieve efficient airway transduction. We hypothesized that differences in transduction between these two systems were because of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…As such, transduction of F508del overexpressing cells with rAAV2‐eGFP was significantly enhanced compared with wild type (WT)‐CFTR cells . Similarly, proteasome inhibitors co‐delivered with rAAV in mice, dogs, and ferrets led to enhanced transduction . They are postulated to enhance transduction by preventing degradation of rAAV capsids, although their exact mechanism remains unknown .…”
Section: What Have Cf Mouse Models Taught Us About Gene Therapy?mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, transduction of F508del overexpressing cells with rAAV2‐eGFP was significantly enhanced compared with wild type (WT)‐CFTR cells . Similarly, proteasome inhibitors co‐delivered with rAAV in mice, dogs, and ferrets led to enhanced transduction . They are postulated to enhance transduction by preventing degradation of rAAV capsids, although their exact mechanism remains unknown .…”
Section: What Have Cf Mouse Models Taught Us About Gene Therapy?mentioning
confidence: 99%
“…73 Similarly, proteasome inhibitors co-delivered with rAAV in mice, dogs, and ferrets led to enhanced transduction. 74,75 They are postulated to enhance transduction by preventing degradation of rAAV capsids, although their exact mechanism remains unknown. 76 These studies point out the complexity of predicting in vivo efficacy as many factors influence this process, including inflamed CF airways and subcellular stress caused by specific CFTR mutations or infections.…”
Section: Andmentioning
confidence: 99%
“…However, in vivo transduction with rAAV2/1 was significantly enhanced by the addition of 200 lM doxorubicin in the vector inoculum. 136 When the infections were conducted in 5-and 12-day-old ferrets, transgene expression was observed in the tracheobronchial epithelium, bronchioles, and scattered alveolar cells, whereas transgene expression was significantly lower in 18-day-old animals and undetectable in adult animals. 136 Interestingly, the resistance to rAAV2/1 transduction in older ferrets appears to be due, at least in part, to the increased abundance of a secreted inhibitory factor(s) in the ferret airway.…”
Section: Gene Transfer To Ferret and Pig Airways Using Raavmentioning
confidence: 98%
“…136 When the infections were conducted in 5-and 12-day-old ferrets, transgene expression was observed in the tracheobronchial epithelium, bronchioles, and scattered alveolar cells, whereas transgene expression was significantly lower in 18-day-old animals and undetectable in adult animals. 136 Interestingly, the resistance to rAAV2/1 transduction in older ferrets appears to be due, at least in part, to the increased abundance of a secreted inhibitory factor(s) in the ferret airway. The identity of the secreted inhibitory factor(s) remains unknown; however, resistance of the airway to rAAV1 infection appears to develop at 18 days after birth, a time point when submucosal glands are nearing a mature state in ferrets.…”
Section: Gene Transfer To Ferret and Pig Airways Using Raavmentioning
confidence: 98%
“…[35][36][37][38][39] We have also demonstrated that the airways of newborn ferrets can be efficiently transduced by rAAV1 in the presence of proteasome inhibitors. 40 Thus, preclinical studies in the CF ferret model can be initiated as soon as an rAAV vector that effectively expresses CFTR in airway epithelium is generated. To this end, we have attempted to optimize an rAAV vector cassette that efficiently expresses the ferret CFTR (fCFTR) gene.…”
Section: Introductionmentioning
confidence: 99%